2019
DOI: 10.1029/2019gc008289
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Olivine CPO and Deformation Parameters in Naturally Deformed Rocks and Implications for Mantle Seismic Anisotropy

Abstract: We analyze peridotites from a wide range of tectonic settings to investigate relationships between olivine crystallographic preferred orientation (CPO) and deformation conditions in naturally deformed rocks. These samples preserve the five olivine CPO types (A‐ through E‐type) that rock deformation experiments have suggested are controlled by water content, temperature, stress magnitude, and pressure. The naturally deformed specimens newly investigated here (65 samples) and compiled from an extensive literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 151 publications
(261 reference statements)
4
54
1
Order By: Relevance
“…This is counter to our natural samples, which do not show strong correlations between texture strength and shear strain ( Figure 6; Skemer et al, 2010;Warren et al, 2008). Olivine CPOs from other peridotite localities (e.g., Ben Ismaïl & Mainprice, 1998;Bernard et al, 2019) also exhibit similar texture strengths to our samples, though strain is unquantified in these examples. The overprediction of texture strength by the Hansen, Conrad, et al (2016) model is observed in other texture models (e.g., VPSC in Signorelli & Tommasi, 2015).…”
Section: The Influence Of a Preexisting Cpocontrasting
confidence: 99%
“…This is counter to our natural samples, which do not show strong correlations between texture strength and shear strain ( Figure 6; Skemer et al, 2010;Warren et al, 2008). Olivine CPOs from other peridotite localities (e.g., Ben Ismaïl & Mainprice, 1998;Bernard et al, 2019) also exhibit similar texture strengths to our samples, though strain is unquantified in these examples. The overprediction of texture strength by the Hansen, Conrad, et al (2016) model is observed in other texture models (e.g., VPSC in Signorelli & Tommasi, 2015).…”
Section: The Influence Of a Preexisting Cpocontrasting
confidence: 99%
“…The most common, A-type LPO regime [Karato et al, 2008;Mainprice, 2007] appears most prevalent among xenolith and mantle massif samples [Ben Ismail and Mainprice, 1998;Bernard et al, 2019]. The corresponding modeled LPO predictions of best-fit hexagonal symmetry axis alignment in flow are broadly consistent with the orientation of the longest FSE axis.…”
Section: Mantle Circulation Modelingmentioning
confidence: 58%
“…If we consider the range of natural xenolith and ophiolite samples, all of the LPO types documented in the lab are indeed found in global compilations [Mainprice, 2007;Bernard et al, 2019]. However, samples from individual sites show a range of different LPOs, at presumably similar deformation conditions in terms of volatile content and deviatoric stress.…”
Section: Formation Of Olivine Lpomentioning
confidence: 92%
See 2 more Smart Citations